The clinical method in geriatrics - Ángel Julio Romero Cabrera; Alfredo Darío Espinosa Brito (Medisur, 2010)
Population aging and the distinctive characteristics of elderly require a particular implementation of the clinical method. Taking into account the special health problems of elderly, the geriatric evaluation is the cornerstone for the medical attention of these patients in the implementation of a global dimension of the clinical method. This article addresses the particular features of the clinical method and the steps to be followed when assisting the elderly.